Cambridge companion to modern Indian culture - Dalmia, Vasudha; Sadana, Rashmi (Cambridge companions to culture, 2012)
"India is changing at a rapid pace as it continues to move from its colonial past to its globalised future. This Companion offers a framework for understanding that change, and how modern cultural forms have emerged out of very different histories and traditions. The book provides accounts of literature, theatre, film, modern and popular art, music, television and food; it also explores in detail social divisions, customs, communications and daily life. In a series of engaging, erudite and occasionally moving essays the contributors, drawn from a variety of disciplines, examine not merely what constitutes modern Indian culture, but just how wide-ranging are the cultures that persist in the regions of India. This volume will help the reader understand the continuities and fissures within Indian culture and some of the conflicts arising from them. Throughout, what comes to the fore is the extraordinary richness and diversity of modern Indian culture"--